The Writer In-between: A Post-phenomenological Analysis of Large Language Models (LLMs) and their Implications for Writer-Tool Relations - Yaghoobian, Hamed (Journal of Human-Technology Relations, 2025)
This article explores the evolving dynamics between writers and their tools within the framework of AI-driven generative word processors, employing a post-phenomenological approach. It argues that despite the shift in complexity from user to tool—facilitated by advancements in technology such as Large Language Models (LLMs)—the interaction between writer and tool remains deeply reciprocal and co-constitutive. This relationship challenges traditional dichotomies of user versus tool, ancient versus contemporary, and digital versus non-digital, advocating for a nuanced understanding that transcends binary categorizations. Drawing upon post-phenomenology, the paper illustrates how even conventional technologies like pens engage writers in a mutual shaping process, suggesting that the essence of writing technology is not in the tool itself but in the relationality it fosters. This interaction suggests a move towards a livelier and less humanist ontology that embraces the complex intimacies and capacities of machine-human connections. We advocate for a framework that permits post-optimal analyses of relationality and fosters extended interactions across diverse milieus. Ultimately, the paper calls for a reconsideration of digital creation stewardship, emphasizing the need for an ethical framework that accommodates the profound implications of AI integration in writing and beyond, highlighting the capacity of writing machines for prodigious generation within these intimate and unfolding encounters.